EFEITO DA ATIVIDADE DE DRAGAGEM SOBRE A MACROFAUNA BÊNTICA DO COMPLEXO PORTUÁRIO DE SÃO LUÍS, MARANHÃO. - SOUSA, Lorena Karine Santos (2018)
This study evaluated the effect of dredging activities on the structure of the macrobenthic community of the São Luis Port Complex (Maranhão, Brazil). Samplings took place in four moments (pre-dredging, dredging 1 with 25% and dredging 2 with 75% and one after the dredging), in 8 sample stations, and at each point 3 samples were collected for analysis of benthic macrofauna, metals and granulometry. A total of 236 organisms were founding, including 89 pre-dredging, 84 dredging 1, 28 dredging 2 and 35 post-dredging. Therefore, there was a decrease in the number of organisms as dredging operations took place. The most representative taxa were Polychaeta, Oligochaeta, Crustacea and Mollusca, highlighting within the group Polychaeta Lumbrineris sp. as the most abundant and present in all campaigns. The metals manganese and zinc in the water column were above the limits allowed by the current legislation (CONAMA Rule 357/2005) while the metals analyzed for sediment, arsenic, copper, chromium, lead, nickel and zinc meet the standards (Rule CONAMA 454/2012). Margalef richness and Shannon-Weaver diversity were higher in pre and post-dredging campaigns, with reduction in dredging campaigns 1 and 2. Principal Component Analysis showed that the abundance of benthic macrofauna correlated with grain size and the sediment metals. Thus, we can conclude that dredging caused a reduction of the benthic macrofauna community, and that despite the recovery of fauna, between dredging and post-dredging campaigns, this was not enough to restore the local community. During the development of the work a new species of Cossura Webster & Benedict, 1887, it was also described. Important for Maranhão, since the Polychaeta fauna is still little known and the taxonomic studies are scarce, and more studies of fauna surveys are needed, since the group must present a much greater diversity than the one known.